$$\sum_{i=1}^{n}\binom{n}{i}\frac{i-1}{i} = 2^n-1-\sum_{i=1}^{n}\binom{n}{i}\frac{1}{i}$$
y:
$$\begin{eqnarray*}\sum_{i=1}^{n}\binom{n}{i}\frac{1}{i}&=&\sum_{i=1}^{n}\binom{n}{i}\int_{0}^{1}x^{i-1}\,dx = \int_{0}^{1}\frac{(1+x)^n-1}{x}\,dx\\&=&\int_{0}^{1}\frac{(2-x)^n-1}{1-x}\,dx=\sum_{j=0}^{n-1}\int_{0}^{1}(2-x)^j\,dx\\&=&\sum_{j=0}^{n-1}\frac{2^{j+1}-1}{j+1}=\sum_{i=1}^{n}\frac{2^i-1}{i}=\sum_{i=1}^{n}\frac{2^i}{i}-H_n \end{eqnarray*}$$
de modo que su límite es:
$$ \lim_{n\to +\infty}\left(\frac{n}{n-1}\right)^2\cdot\left(1-\frac{H_n+1}{2^n}-\sum_{i=0}^{n-1}\frac{1}{(n-i) 2^{i}}\right)=\color{red}{1}$$
desde:
$$ \sum_{i=0}^{n-1}\frac{1}{(n-i)2^i}\leq\sum_{i=0}^{n-1}\frac{1}{(n-i)(1+i)}=\frac{1}{n+1}\sum_{i=0}^{n-1}\left(\frac{1}{i+1}+\frac{1}{n-i}\right)=\frac{2H_n}{n+1}.$$